BeiDou/GPS relative kinematic positioning in challenging environments including poor satellite visibility and high receiver velocity. Issue 371 (3rd March 2020) - Shi, Junbo; Huang, Yongshuai; Ouyang, Chenhao; Lu, Xingning; Xu, Chaoqian
Abstract : Global Positioning System (GPS) satellite tracking loss always occurs under challenging observation conditions such as poor satellite visibility, high receiver velocity and so on. The announcement of China's BeiDou Navigation Satellite System (BDS) regional service in 2012 has, on one hand, provided a new standalone positioning system and, on the other hand, augmented GPS under challenging observation conditions. This paper carries out BDS/GPS relative kinematic positioning with poor satellite visibility and high receiver velocity including an under-foliage pedestrian positioning at the speed of ∼5 km h −1, a city urban vehicle positioning at the speed of ∼30 km h −1, and an open-sky air vehicle positioning at the speed of ∼130 km h −1 . Numerical results reveal that the standalone system cannot always provide reliable kinematic positioning solution in challenging observation environments. Instead, BDS/GPS combined system can provide better kinematic performance, i.e. 94.2% solution with 0.251 m precision (1-sigma) for the under-foliage pedestrian scenario and 97.0% solution with 0.151 m precision (1-sigma) for the city-urban vehicle scenario. As for the high receiver velocity case, both BDS and GPS can provide cm-level kinematic positioning precisions from the perspective of aerial photogrammetry. The BDS/GPS combined system cannot further improve the positioning availability and precision too much.